Analysis of Changing Population Age Structures in the Districts of Peninsular Malaysia from 2000 to 2010: Analisis Perubahan Struktur Umur Penduduk di Daerah Semenanjung Malaysia dari Tahun 2000 hingga 2010 - Hamzah, Fazreen Nur; Rainis, Ruslan (GEOGRAFI, 2022)
Population growth trends cause changes in population size, which are influenced by births, deaths, and migration. However, since the sources of population growth are not precisely known, it is difficult to identify which areas receive the contribution of population growth. Therefore, this study aims to determine the sources of population growth in the districts of Peninsular Malaysia between 2000 and 2010. Data on the age structure of the population were analysed using the shift-share method. The results of the shift-share analysis show that the Federal Territory of Kuala Lumpur is the largest contributor to population growth at the national level, while Cameron Highlands is the smallest contributor to population growth at the national level. Hence, it can be concluded that the methodology used in this study is useful in analysing changing population age structures, thus helping stakeholders in formulating, and implementing plans for more effective district development, so that the balance of population growth can be achieved.